Environmental dilemma and sustainable development of resource-based cities: A case study from northeast china - Qing, Yiting; Guo, Wei; Cao, Gaohang; Qin, Yu; Nie, Xin; Wang, Han (Frontiers in Environmental Science, 2022)
With ambitious carbon peak and carbon neutral targets, China has to realize it relies heavily on significant reductions in energy-related carbon emissions. Therefore, as the largest contributing region, resource-based cities (RBCs) must achieve an energy transition. Unfortunately, these cities are facing serious environmental problems. The aim of this study is to analyze the development history and problems of RBCs by using the example of the Northeast region. The results show the reasons blocking the green development of these cities include management policies and life cycles. This implies the management of RBCs needs to develop toward a win-win situation of industrial transformation and ecological protection. Finally, some policy recommendations are proposed to achieve emission reduction and sustainable development.